Implementasi Sistem Monitoring Berbasis IOT Pada Peternakan Ayam Alfarizi Palembang - Wijaya, Hari; Rini, Arsia; Azro, Isnainy (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
Alfarizi Farm is one of the farms in Palembang located on Jalan Jakabaring, Silaberanti Village, Jakabaring District, Palembang City, South Sumatra. The chickens raised include broiler chickens, local chickens, and layer hens. The lack of adequate facilities to handle stress in chickens also poses a challenge in maintaining stable temperatures on the farm. Many farmers still use conventional methods, such as estimating the temperature based on their feelings about the heat inside the coop, resulting in manual temperature and humidity control that is not always accurate. In addition, the manual temperature monitoring and regulation system also consumes a lot of time and effort for farmers. Therefore, it is necessary to build a control system aimed at reading the temperature and humidity inside the barn using DHT22 sensors, then the data will be sent to the ESP32 microcontroller. If the temperature is detected to be too high, the system will automatically activate a fan to cool the barn, and if the temperature is too low, a heating lamp will be turned on. All obtained data will be sent to the IoT platform, namely Blynk, which allows farmers to monitor the barn conditions directly through a web-based or smartphone application. Keywords—Temperature monitoring, Humidity, Alfarizi farming.